Voluntary vs. mandatory approaches to nonpoint pollution control: Complements or substitutes? - Kathleen Segerson (Fondazione Eni Enrico Mattei (FEEM), 1998)
This paper develops a simple economic model of the interaction between a regulator and farmer that allows us to analyse the use of a policy that combines a voluntary, cost-sharing approach to improving water quality with a background threat of imposition of mandatory controls or taxes if the voluntary approach is unsuccessful in meeting a pre-specified water quality goal. In particular, we use the model to examine the conditions under which a welfare-maximising regulator would want to offer such a policy to farmers, and whether the regulator can use such a policy to induce cost-minimising abatement decisions without the need for farm-specific information about pollution-related characteristics that would be needed to implement first best mandatory policies (such as ambient taxes). We first consider the simpler case where there is a single farm in a given watershed. We then extend the analysis to consider multiple farms, and ask whether the policy can be designed to avoid free-riding in this context. The results suggest that, under a (credible) threat of imposition of a mandatory mechanism that will induce cost-minimising abatement decisions, the regulator can use a uniform subsidy rate (i.e., a rate that does not depend on farm characteristics) to induce participation in a voluntary program to achieve a given water quality goal. Thus, it is possible to induce first-best abatement decisions by heterogeneous farms without knowing farm-specific characteristics or tailoring the subsidy rate to the farm type. Whether a welfare-maximising regulator would want to establish a voluntary program of this type depends on the magnitude of the transactions costs associated with implementing a first-best mandatory instrument, the likelihood that a mandatory approach would be imposed if there is no voluntary approach or if a voluntary approach is unsuccessful, and the social cost of funds used to finance any subsidy that is paid for participation in a voluntary approach.
Keywords: 330; Umweltpolitik; Selbstverpflichtung; Kleinbäuerliche Landwirtschaft; Regulierungstheorie; Theorie